(untitled) (International Journal of Engineering and Computer Science, 2015)
This white paper will help service providers understand the benefits and economics associated with implementing a Next Generation Network (NGN). Convergence is the process of interconnection of traditional switched circuit networks (the PSTN and mobile networks) and packet-switched networks based on the Internet Protocol (IP) for routing.